2012
DOI: 10.1089/chi.2011.0090
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Physical Activity, and Sedentary Behaviors as Risk Factors for Childhood Obesity: An Urban and Rural Comparison

Abstract: The persistently higher odds of overweight and obesity among rural children even after adjustment suggest that rural environments may be "obesogenic" in ways that a person-level analysis cannot discern. Future research should examine disparities in the accessibility and affordability of healthy food and beverage choices and safe physical activity locales in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 36 publications
4
105
2
1
Order By: Relevance
“…Obesity rates tend to be highest among children in families who function at or below the poverty threshold (2). While studies have found higher than average prevalence of obesity in urban youth (3), comparative studies indicate that children residing in rural areas also run higher than average risk of obesity (4,5) with children in rural areas having up to 30% greater chance of being overweight or obese than children in non-rural areas even after adjustments for sociodemographic, health, diet and exercise (6).…”
Section: Introductionmentioning
confidence: 94%
“…Obesity rates tend to be highest among children in families who function at or below the poverty threshold (2). While studies have found higher than average prevalence of obesity in urban youth (3), comparative studies indicate that children residing in rural areas also run higher than average risk of obesity (4,5) with children in rural areas having up to 30% greater chance of being overweight or obese than children in non-rural areas even after adjustments for sociodemographic, health, diet and exercise (6).…”
Section: Introductionmentioning
confidence: 94%
“…These studies have revealed mixed findings by age. For example, data from a nationally representative study showed that older rural children (12-19 years) had 30% higher odds of being overweight or obese compared to urban children, although no significant differences were observed in younger children (2-11 years) 10 . A recent meta-analysis using data of US children aged 2-19 years found that rural children compared to urban children are 26% more likely to be obese (odds ratio (OR)=1.26; 95% confidence interval (CI)=1.21-1.32)…”
mentioning
confidence: 99%
“…Consistently, rural children are more likely to be overweight or obese compared to urban children after controlling the socio-demographic characteristics, health and obesity-related behavioral factors. This significant difference is found both in boys and girls (Liu et al, 2010).…”
Section: Rural Residency As a Health Indicatormentioning
confidence: 70%
“…S. Brown et al, 2007). Further, evidence indicates that children in rural areas are more likely to be overweight or obese, and participate in unhealthy behaviors (Liu, Bennett, Harun, & Probst, 2008;Liu et al, 2010). Childhood is a crucial time when healthy behaviors are learned and adopted, and early childhood intervention programs can make a significant difference to a child's life changes (Gray & Francis, 2007).…”
Section: Need For the Studymentioning
confidence: 99%
See 1 more Smart Citation